Development of a Cloud-Native Student Activity Management Information System at Politeknik Negeri Medan - Darmeli Nasution; Indri Sulistianingsih; Alex Sandro Dabukke; Sri Wahyuni; Bayu Putra Pratama (Journal of Information Technology, computer science and Electrical Engineering, 2025)
Politeknik Negeri Medan, like many higher education institutions in Indonesia, encounters persistent challenges in managing non-academic student activities due to fragmented data repositories, inconsistent reporting mechanisms, and manual administrative workflows. This study proposes the design of a cloud-native Student Activity Management Information System (SAMIS) engineered to streamline the processes of planning, monitoring, verification, and evaluation of extracurricular activities. The system adopts a microservices-based architecture supported by containerization, Kubernetes orchestration, and CI/CD pipelines to ensure scalability, resilience, and operational efficiency. Key functional modules include proposal submission, multi-level review workflows, real-time activity tracking, and centralized document management. Although the system has not yet been implemented, architectural simulations, workflow modelling, and comparative analysis with previous studies indicate strong potential for improving institutional governance and supporting data-driven decision-making. The proposed design also aligns with contemporary digital transformation initiatives in higher education. Future work includes prototype development, pilot testing, and comprehensive user evaluation to validate performance in real-world contexts.